1993
DOI: 10.1093/oxfordjournals.humrep.a138228
|View full text |Cite
|
Sign up to set email alerts
|

Immunology: Evidence for the in-vitro de-novo synthesis of immunoglobulin and a previously undescribed 17 kDa protein (TEP-2) by the mucosa of the Fallopian tube

Abstract: De-novo synthesis and secretion of proteins by short-term explants of matched Fallopian tube mucosa and endometrium were studied using radiolabelled L-[35S]methionine and [3H]glucosamine. To compare directly each anatomical site of the Fallopian tube and endometrium from the same source, newly synthesized proteins were separated on one-dimensional polyacrylamide gel electrophoresis and examined by auto-radiography. De-novo synthesis of two protein bands provisionally designated as tubal epithelial protein 1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Another specific feature of tubal fluid is the presence of oviductspecific glycoproteins with their highest levels observed in the peri-ovulatory phase. Using radiolabelled L-[35S] methionine and [3H]glucosamine, investigators have been able to identify and isolate two proteins, named Tubal Epithelial Protein 1 and 2 (TEP-1 and TEP-2) that were exclusively produced by the tubal explants from premenopausal women and were absent in similar explants' secretions from postmenopausal women [75,76] . Although the biological role of these proteins is not well established, it has been suggested that their production and secretion is enhanced in response to estrogenic stimulation [77].…”
Section: Tubal Fluidmentioning
confidence: 99%
“…Another specific feature of tubal fluid is the presence of oviductspecific glycoproteins with their highest levels observed in the peri-ovulatory phase. Using radiolabelled L-[35S] methionine and [3H]glucosamine, investigators have been able to identify and isolate two proteins, named Tubal Epithelial Protein 1 and 2 (TEP-1 and TEP-2) that were exclusively produced by the tubal explants from premenopausal women and were absent in similar explants' secretions from postmenopausal women [75,76] . Although the biological role of these proteins is not well established, it has been suggested that their production and secretion is enhanced in response to estrogenic stimulation [77].…”
Section: Tubal Fluidmentioning
confidence: 99%
“…Previously, using the proteomics approach, the FT luminal secretion was studied using in vitro primary epithelial cell culture due to the lack of ideal in vivo interventions to collect real-time secretions. The tubal secretome contains many bioactive compounds including glucose, lactate, pyruvate, various other metabolites, amino acids [116] , and certain FT-specific proteins such as TEP-1 and TEP-2 [117] . Moreover, the human FT expresses activin βA- and βB-subunits, activin type IIA and IIB receptors, and follistatin when the peak secretions can be found during the luteal phase that encompasses early embryo development and transit.…”
Section: Ft “Omics” In Understanding Early Embryo-maternal Interactionsmentioning
confidence: 99%